Comparison of coagulation performance using natural coagulants against traditional ones. Issue 10 (3rd July 2021) - ELsayed, E. M.; Nour El-Den, A.A.; Elkady, M. F.; Zaatout, A. A.
ABSTRACT: Coagulation performance of different seeds' extracts, namely, (Bean, Lima bean, Lentil, and Fenugreek) were evaluated using synthetic turbid water. The coagulation active agents were extracted from the crushed seeds using different types of solvents like sodium chloride and sodium hydroxide solutions with different molarities. Batch coagulation experiments were conducted to evaluate the activity of the extracted bio-coagulants for water decontamination. The coagulation effectiveness of the seeds' extracts has been compared with that of alum. The highest % turbidity removal using Fenugreek was 98% while that of alum was 85%. Thus, using Fenugreek as plant-based natural coagulants is a promising alternative toward sustainable water clarification.